THE LIFE PROJECTS OF THE CHILDREN OF BABASSU EXTRACTIVISTS IN MARANHÃO, BETWEEN CONTINUITIES AND RUPTURES - Silva, Maria de Fatima Sousa [UNESP]; Aragao, Jose Euzebio de Oliveira Souza [UNESP] (Centro Univ Nove Julho, 2023)
This work is part of a doctoral research, which aimed to know the life projects of teenagers, children of babassu coconut breakers in eastern Maranhao, in an attempt to understand if in their projects is the continuity of the activities realized by their families or turn to other professional activities. The research is part of a doctoral thesis and had the participation of thirteen teenagers who attended the 8th and 9th year of elementary school in a public school in the rural area of Maranhao, children of babassu coconut extractivists, as well as other collaborators who work in education, but only the ones will be mentioned here. The research revealed that the school where they study does curricular axis, striving to strengthen their life projects, there is theoretical support in the perspective of Freire's teaching. It is noteworthy that the school interferes with their life projects, as both students and parents see it as an alternative for better economic and social conditions. Therefore, from the study, it was also evident that these teenagers have as their main target in their life projects, a higher education academic training to have a good profession that is not related to the activities of babassu coconut.
Keywords: rural teenagers; coconut babassu; life project